Periodic Oscillations in the Stratosphere and Mesosphere. - Cole ,Allen E.; Kantor,Arthur J. (1974)
Periodic fluctuations in the annual temperature and density distributions based on rocket observations at heights between 30 to 90 km are presented in terms of amplitude and phase as a function of height and latitude. The phases of the semi-annual components in arctic and subarctic regions are markedly different at levels in the upper stratosphere if the analyses are based on monthly medians rather than monthly means. Means and medians are considerably different at these altitudes during the winter months in this region due to stratospheric and mesospheric warmings.